HUBUNGAN PERILAKU PICKY EATER DENGAN STATUS GIZI PADA ANAK USIA PRA SEKOLAH - Wahyuningsih, Sri; Anggraini, Marisa Lia; Rosa, Audrey Faiza (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The prevalence of monitoring the nutritional status of children in the city of Padang in 2017 states that the District Pauh has the highest number of 300 undernourished people. Known nutritional status data by category BB / U is a toddler with undernourishment by 60 (20%). Malnutrition caused because eating one of which is the behavior of a picky eater. Picky eater occurs in pre-school age children experience changes in eating patterns generally picky eating. Behavior picky eater is a risk of the child may experience problems nutritional status. The purpose of this study was to determine the behavior of Picky Eater Relationship with Nutritional Status on Preschooler in kindergarten Al Hidayah Village Padang Pauh Subdistrict Cupak Tangah 2019.This type of research analytic survey with cross sectional study. The sampling technique is